(untitled) (Third Sector Social Economic Review, 2021)
This study reveals the consumers’ attitude towards the use of national and cultural values portrayed in commercials aired on TV in Turkish market and also reveals the consumers’ potential reactions to these message. The use of national and cultural values in television advertisements is discussed in terms of different dimensions in different studies. In this field, where researchers generally preferred the content analysis method, the authors used phenomenological research design and in-depth interview methods, and in-depth interviews were conducted with 11 participants with a questionnaire consisting of 13 questions. The results showed that, consumers felt closer to brands that use cultural and national values in their advertisements, and in addition, it was observed that consumers agreed that using these values respected cultural and national values. This feeling makes communication with the consumer much easier for brands and creates a positive bond between brands and consumers. It is also observed that, consumers are close to brands that respect their national and cultural values, support them in order to keep these values alive, advocate these brands and prefer these brands to meet their needs.